'I Knew I Should Stop, but I Couldn't Control Myself': a qualitative study to explore the factors influencing adolescents' consumption of sugar-sweetened beverages and sugary snacks from a socio-ecological perspective. Issue 9 (18th September 2022) - Wang, Chia-Wen; Chen, Duan-Rung; Chan, Chang-Chuan; Yeh, Yen-Po; Chen, Hsiu-Hsi
Abstract: Objective: To explore the factors influencing Taiwanese adolescents' consumption of sugar-sweetened beverages (SSB) and sugary snacks from a socio-ecological perspective. Design: This study adopted a qualitative design by using face-to-face, in-depth interviews guided by a semistructured questionnaire. Setting: Eight junior high schools in New Taipei City and Changhua County, Taiwan, September to November 2018. Participants: Fifty-nine participants aged 12–14 years participated in this study. Results: Reflexive thematic analysis was used to analyse the data. This study identified four themes to address the multifaceted factors that influence adolescents' consumption of SSB and sugary snacks. At the intrapersonal level, physiological factors, psychological factors, individual economic factors and taste preferences were mentioned in connection with people's consumption of SSB and sugary snacks. Positive or negative influences of parents, siblings, peers and teachers on SSB and sugary snack intake were identified at the interpersonal level. The availability of SSB and sugary snacks at home, their availability in vending machines or in school stores in the school environment and participants' access to convenience stores and hand-shaken drink shops in the broader community influenced SSB and sugary snack consumption. Additionally, food culture and food advertising were identified as influencing societal factors. Conclusions: Overall, this qualitative study determined not only that the consumption of SSB and sugary snacks is influenced by intrapersonal factors but also that interpersonal, environmental and societal factors affect adolescents' increased sugar intake. The findings are helpful to broaden the options for designing and developing interventions to decrease SSB and sugary snack consumption by adolescents.